ACCOUNTING IN INSURANCE ORGANIZATIONS: INTERNATIONAL OPERATIONS (International Congress on Economics, Management and Business Studies, 2026)
The organization of business processes operating in our republic on the basis of international standards requires consideration of the level of organization of the accounting and audit system, similar to that in developed countries. The audit process covers all aspects of auditing standards. In particular, the more reliable the evidence collected by the auditor is, the more important and accurate the conclusions drawn.